A Rare Case of Chronic Uterine Inversion Secondary to Submucosal Fibroid Managed in the Province Hospital of Nepal - Amit Singh; Rajan Ghimire (Case Reports in Obstetrics and Gynecology)
Uterine inversion secondary to uterine pathology is a rare scenario that a gynecologist encounters. Unlike puerperal uterine inversion, it is misleading and may not always be possible to reduce to normal position without surgery. We report a case of a 35-year female with per vaginal bleeding for fifteen months with a mass-like sensation in the vaginal canal. She presented in shock and had a globular mass in the vaginal canal with the indistinct cervical os. She was resuscitated with blood transfusions and intravenous fluid. She was posted for emergency surgery where myomectomy was done vaginally, and finally, Haultain’s procedure was carried out. The uterus was preserved.